Anti-ribosomal P2: could it be a useful new criterion for patients with systemic lupus erythematosus? - Menna N. Hemdan; Tayseer Khedr; Samar H. Goma; Fatma Mohammed Helbawi Mohammed; Maha S. I. Abdelrahman (Egyptian Rheumatology and Rehabilitation)
Abstract Background Systemic lupus erythematosus is a multisystem autoimmune disorder that displays numerous autoantibodies such as anti-nuclear, anti-Smith, anti-double-stranded DNA, and anti-ribosomal antibodies. Anti-ribosomal antibodies are detected in 15 to 40% of systemic lupus erythematosus patients. We aimed to study anti-ribosomal P2 to find its diagnostic utility and determine how it could be associated with different clinical manifestations. Results This observational case control study included 50 lupus patients and 35 healthy controls with a mean age of 32.92 ± 8.66 versus 35.43 ± 10.19 years, respectively. We observed that 10 cases out of 50 (20.0%) had positive anti-ribosomal P2 versus two healthy subjects (5.7%) (P = 0.111). The anti-ribosomal P2 biomarker had a sensitivity of 20.0% and a specificity of 94.3% for systemic lupus erythematosus detection. Neuropsychiatric manifestations were observed in 5 out of 10 cases with positive biomarker compared to 6 out of 40 cases with negative anti-ribosomal P2 antibody (P = 0.030). Conclusion The anti-ribosomal P2 antibody has high specificity and low sensitivity for systemic lupus erythematosus. It is closely linked to the pathogenesis of neuropsychiatric lupus. Further studies are required to assess anti-ribosomal antibody subunits’ diagnostic and clinical value.